KOMPETENSI GURU DALAM MENGELOLA PEMBELAJARAN AL-QUR’AN HADIST DI MAS SYEKH AHMAD BASYIR PARSARIRAN BATANG TORU - HERMAN PELANGI (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
This study discusses the problem of teacher competence in managing learning Al-Qur'an Hadist in MAS Sheikh Ahmad Basyir Parsariran Batang Toru. Researchers chose this title because the researchers saw the weakness of Al-Qur'an Hadist teachers in managing learning. The formulation of this research problem is how the competence of teachers in managing learning Al-Qur'an Hadist in MAS Sheikh Ahmad Basyir Parsariran Batang Toru and what efforts of teachers Al-Qur an Hadist in managing learning in MAS Sheikh Ahmad Basyir Parsariran Batang Toru. The purpose of this study is to know how the competence of Al-Qur'an Hadist teachers in managing learning in MAS Sheikh Ahmad Basyir Parsariran Batang Toru and To find out what efforts of teachers Al-Qur'an Hadist in managing learning in MAS Sheikh Ahmad Basyir Parsariran Batang Toru . The research method used by using descriptive qualitative method while the techniques and data collection tools used are interviews (interviews) and observation and documentation, while the analysis of data in executed by compiling and mengola data, then describe it systematically. After collecting the data, processing the data and analyzing the data from the research that has been done, the researchers get the result that the competence of teachers in managing learning Al Qur'an Hadith in MAS Sheikh Ahmad Basyir Parsariran Batang Toru, is in the low category, because it is still less in megadakan pretest, lack of use of learning methods, neglect of learning objectives (TPK), lack of media use, and lack of follow-up learning. Efforts are made in the formation of teacher competence in managing the learning of the Qur'an Hadiśt in MAS Sheikh Ahmad Basyir Parsariran Batang Toru is the background of teacher education by suggesting continuing education to a higher level, attending seminars or training, fostering teacher creativity, following the workshop upgrading. Read the relevant books, and will continue education to a higher level, and hold a dialogue with more experienced people to increase their knowledge.